Petal-like CdS nanostructures coated with exfoliated sulfur-doped carbon nitride via chemically activated chain termination for enhanced visible-light–driven photocatalytic water purification and H2 generation - Wu, Yan (2020)
Novel composite photocatalysts consisting of petal-like cadmium sulphide (CdS) nanoparticles and varying amounts of exfoliated sulfur-doped carbon nitride (SCN) were successfully prepared. The as-obtained materials were characterized by field emission scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet–visible diffuse reflection spectroscopy, photoluminescence spectroscopy and photocurrent-time measurement. Results indicate a strong electric coupling interaction between SCN and CdS due to the heterojunction formed at the amine functionalities sites and oxidized chain terminations of SCN. Two typical pollutants like rhodamine B (RhB) and colorless bisphenol A (BPA) were used for the evaluation of photocatalytic activity. The best-performing CdS/SCN composite (i.e., CS5) synthesized exhibited enhanced visible-light-driven photocatalytic RhB efficiency of about 8.71 and 4.06 times higher than those of pure exfoliated SCN and CdS, respectively. As for BPA degradation, the CS5 composite was 9.00 and 3.61 times more efficient than that of exfoliated SCN and CdS, respectively. These excellent performances were found to be attributable to the remarkable charge carrier separation between CdS and exfoliated SCN with the aid of heterojunction interfacial structures. More importantly, the exfoliated SCN substantially reinforced the photostability of the CdS nanoparticles. Evaluation of the photocatalytic H2 evolution showed that the visible-light H2 production rate of the best-performing CS5 composite was also much greater than the constituents at 247.72 μmol h−1 g−1. Cyclic tests demonstrated the stability of the CS5 composite over repeated use. A possible mechanism was proposed to explain the photocatalytic reaction process. This study provides new insights into the preparation of highly efficient and stable sulfide-based composite photocatalysts, which are promising for implementation in wide-ranging environmental applications.